Cultivation of Oyster mushroom (Pleurotus ostreatus) and Button mushroom (Agaricus bisporus) utilizing used coffee grounds and rice straw as substrates: Mushroom culture - Shivrattan, Amirah; Seecharran, Diana; Ansari, Abdullah Adil (Mushroom Research, 2022)
This research investigated used coffee grounds, rice straw, and the combination of used coffee grounds and rice straw as substrates to grow Pleurotus ostreatus (Oyster mushroom) and Agaricus bisporus (Button mushroom). The procedure consists of four (4) main phases: preparation of mushroom mother culture with potato dextrose agar, preparation of stock spawn, preparation of mother culture of substrates, and harvesting. The elemental analysis (Nitrogen, phosphorous, and potassium) of the mushrooms’ fruiting body and the initial and final substrates were done by the Guyana Sugar Corporation (GUYSUCO). P. ostreatus and A. bisporus were successfully cultivated in the rice straw substrate but not in the used coffee ground substrate and the combination of used coffee grounds and straw substrate.